The Isoelectric Point and the Surface Charge of Barium Titanate Nanoparticles/Graphene Oxide Determined Using the Electrophoretic Mobility Technique - Anh, Vuong Thi Vy; Dung, Nguyen Thi; Chau, Chu Ngoc; Mai, Phan Thi Tuyet; Hoan, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 1DO - 10.25073/2588-1140/vnunst.5114, 2021)
Barium titanate nanopowders, and composite materials of barium titanate/ graphene oxide (10 wt.% of graphene oxide according to the initial composite composition) were synthesized by hydrothermal method at the fixed reaction condition of 200 o C and 24 hours. The obtained powders were characterized by different techniques: X-ray diffraction, FTIR spectroscopy, Particles size distribution, and Scanning electron microscopy. Zeta potential measurement under electrophoretic mobility technique was also employed to investigate the stability of the BaTiO 3 nanoparticles and composite materials of barium titanate/graphene oxide. The results showed that the BaTiO 3 present with the tetragonal crystal structure ( P 4 mm, a = 4.0000 Å, c = 4.0109 Å) and has uniform morphology with the grain sizes are in the range of 70 - 140 nm. The BaTiO 3 nanoparticles were well distribution and covered on a surface of graphene oxide. The BaTiO 3 nanoparticles, and BaTiO 3 /graphene oxide are stable in alkali, neutral media, and acidic media up to pH ~ 5.